Can Smart Contracts Have a Legality Valid in Indonesia? - Berliana, Dina; Dewantara, Reka; Widyanti, Yenny Eta (IJBLE Scientific Publications Community Inc., 2025)
The development of digital technology has encouraged the use of smart contracts as an instrument for automating agreements in Blockchain-based electronic transactions. In the context of Indonesian law, the validity of a smart contract must meet the legal requirements for an agreement, as regulated in Article 1320 of the Civil Code, which includes the agreement between the parties, legal capacity, a transparent object of the agreement, and lawful causes. Additionally, data verification in smart contracts is a key element in guaranteeing the security, authenticity, and transparency of e-commerce transactions, which is related to the provisions in the ITE Law and the PDP Law. This verification aims to prevent data manipulation, reduce the risk of fraud, and increase trust in transactions by using encryption technology, digital signatures, and Blockchain-based identity. Smart contracts can be considered valid if they fulfill the terms of the agreement and data security principles, making their use in e-commerce more effective and reliable.